Research on the Influence of Visual Factors on Emotion Regulation Interaction - Xiong, Zhiyong; Weng, Xinyu; Wei, Yu (Frontiers in Psychology, 2022)
To guide the design direction of emotion regulation products that improve users' positive emotions, studying the correlation between relevant visual factors and multi-dimensional complex emotions is necessary. We use the presented Extended Product Emotion (E-PrEmo) measurement method to describe each influencing factor's multi-dimensional emotional set and calculate their weight according to the order. We compare the positive and negative emotion indicators of all influencing factors and analyze the evaluation and ranking factors that affect users' emotional value of emotion regulation products. The experimental results show that specific emotion mapping scenes on positive emotion are the most significant among the key factors affecting user emotion. Furthermore, the influence of emotional expression, emotional index score, and emotional text description on positive emotions decreased in turn. The influence of emotional text expression on positive emotion is the lowest. Through the study of the visual factors that affect users' psychological emotions, it is helpful to guide the development of emotion regulating products more scientifically and reasonably.